New evidence for the dating and impact of the Black Death in Asia - Hymes, Robert P. (Arc Humanities Press, 2023)
Evidence that the Second Plague Pandemic was already ravaging China by the early thirteenth century - over a century before it made its virulent appearance in the Mediterranean.